Evaluating the ecological impacts of dominant non-indigenous sessile invertebrates in peninsular coastal ecosystems - Ubagan, Michael Dadole; Lee, Taekjun; Kim, Yongeun; Lee, Jeonghee; Jeong, Hoon; Lee, Yun-Sik; Shin, Sook (Frontiers in Marine Science, 2025)
Sessile invertebrates perform essential ecological functions in coastal ecosystems. This study aimed to provide an in-depth analysis of the status and distribution of sessile invertebrates along the peninsular coasts of South Korea, focusing on the potential ecological impacts of non-indigenous species. Fourteen sampling sites along the coastline of the Korean Peninsula were surveyed four times over a year, once in each season, to investigate the subtidal communities of sessile invertebrates. Based on the community data, this study identified indigenous and non-indigenous species and classified them into broadly present and regionally dominant species among geographically distinct coastal ecosystems in Korea. Effects of non-indigenous species on biodiversity within their dominance range were analyzed to identify species with potential significant ecological impacts. Results indicated that while some dominant non-indigenous species had no significant effects, others such as Amphibalanus amphitrite were associated with a loss of biodiversity in the Yellow Sea. This study highlights the importance of clearly distinguishing the range of dominant species and emphasizes the need for continuous monitoring to support early detection and inform management strategies for reducing negative impacts of non-indigenous species. This research provides new insights for assessing the influence of non-indigenous species within sessile invertebrate communities.